Qualities, Prices and Budget Enquiries - Theil, H. (Review of Economic Studies, 1952)
Journal Article Qualities, Prices and Budget Enquiries Get access H. Theil H. Theil Amsterdam Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 19, Issue 3, 1952, Pages 129–147, https://doi.org/10.2307/2296016 Published: 01 January 1952